2010
DOI: 10.1177/1721727x1000800209
|View full text |Cite
|
Sign up to set email alerts
|

Stress Characteristics in Different Work Conditions: Is it Possible to Identify Specificity of Risk Factors by the Questionnaire Method?

Abstract: The aim of this study is to identify, by a brief ad hoc questionnaire, specific dimensions of perceived occupational stress that could be relevant in two different work conditions of female workers: visual display unit (VDU) operators, for whom the risk of work-related stress is already known in literature, and kindergarten teachers, for whom very few studies have examined this risk. A questionnaire, prepared specifically for workers, was filled in by 70 all-female kindergarten teachers and 70 all-female VDU o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Psychosomatic disturbs were also included in this category, because they were considered a consequence and a demonstration of the impairment of mental health. There are many psychiatric disturbs related to mobbing in literature: maladaptive disorders, depression, anxiety, pre-alarm status, obsessions, panic attacks, isolation (27,30,31,32), eating disorders (33), post-traumatic stress disorder (27,32,34), psychosomatic disturbs, stress and generic consequences on mental health (14,17,19,20,35). The heterogeneity is high in all the subcategories, because of the different ways of selection and evaluation mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosomatic disturbs were also included in this category, because they were considered a consequence and a demonstration of the impairment of mental health. There are many psychiatric disturbs related to mobbing in literature: maladaptive disorders, depression, anxiety, pre-alarm status, obsessions, panic attacks, isolation (27,30,31,32), eating disorders (33), post-traumatic stress disorder (27,32,34), psychosomatic disturbs, stress and generic consequences on mental health (14,17,19,20,35). The heterogeneity is high in all the subcategories, because of the different ways of selection and evaluation mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Within atherosclerotic sites, endothelial cells and leukocytes both have increased their expression of numerous adhesion molecules and their receptors, including intracellular adhesion molecule-I, vascular celI adhesion molecule-I,~,-integrin,~~ integrin and P-selectin (118)(119)(120)(121). In vivo studies (122)(123) have shown that blocking these adhesion molecule interactions by the administration of antibodies or gene targeting attenuates the formation of atherosclerotic lesions, indicating a potential therapeutic role for inhibition of leukocyte adhesion and extravasation.…”
Section: Statinsmentioning
confidence: 99%
“…Once a cancer patient is affected by stress, specific pathways within the brain lead to the activation of the hypothalamic-pituitary-adrenal axis as well as the central sympathetic nervous system (3). The stress response consists in releasing key peripheral mediators such as catecholamines and glucocorticoids the role of which in the pathophysiology of chronic stress is extraordinarily complex and controversial (4). Moreover, in cancer, catecholamines can enhance carcinogenic properties of prostate, ovary, breast and colon tumor cells (5), while glucocorticoids are immune-suppressive agents (6).…”
mentioning
confidence: 99%